Contextualized Instructional Video Material on Disaster Readiness and Risk Reduction (DRRR) for Senior High School in Camarines Sur, Philippines (American Journal of Interdisciplinary Research and Innovation, 2025)
This study focuses on creating a Contextualized Instructional Video Material for DRRR (DRRR) for Senior High School in Camarines Sur, Philippines. The research used a descriptive-developmental design, gathering data through questionnaires and interviews to identify the instructional materials currently used by teachers in teaching DRRR. The study found a lack of contextualized instructional materials in Senior High School, which poses challenges in delivering effective lessons. Feedback from DRRR teachers and ICT coordinators highlighted the need for resources that are relevant to the local context. The findings emphasize the importance of developing contextualized instructional materials to address this gap and support effective teaching. The study recommends making these resources easily accessible to enhance student learning and maximize their benefits.